Grade 10 Filipino students' visual art experiences and aesthetic response - Malong, Ian Jule A.
This study explored the aesthetic responses of eight Filipino adolescents and how their experiences with the visual arts influenced these responses. The participants shared their experiences through individual interviews, generating four key themes: (1) Interests in Popular and Western Art Themes, (2) Productive Self-initiated Art Activities, (3) Experiences in the Virtual Art World, (4) Distinct and Overlapping Intentions in Making and Responding to Art. The participants also engaged in an Aesthetic Development Interview, responding to a chosen art stimulus. (1) Naming Responses, (2) Descriptive Responses, (3) Narrative Responses, (4) Criteria-guided Responses, and (5) Signification Responses are the identified categories of responses. Narrative and descriptive responses were most prevalent across participants, regardless of their art activities. Notably, Signification Responses appear to be the most prevalent for the participant with the highest exposure to the visual arts. These findings agree with existing research on common adolescent art responses. The findings also support prior research linking art experiences to individual aesthetic responses. This study highlights a gap in adolescents' knowledge of Filipino artists and their lack of ability to interpret a visual artwork's meaning. These findings are essential, especially for art education, to give more attention to Filipino visual arts and art interpretation as part of learning in the arts. Recommendations include further research on art-related experiences and aesthetic responses involving Filipinos of varied age groups and cultural backgrounds, fostering aesthetic growth through self-initiated art, and delivering meaningful art experiences in the classroom and cyberspace.